Exploring The Roots of Human Development: The Role of Poverty, Unemployment, and Educatiion in Indonesia - Susilawati; Abdul Haris (Jurnal Magister Ekonomi Syariah, 2026)
The Human Development Index (HDI) is a measure of the level of community welfare as seen from three main indicators, namely education, health, and income. The HDI is an important benchmark in assessing the quality of life of the community and the effectiveness of a country's development. One of the strategic efforts to improve the quality of life of the Indonesian people is to pay attention to socio-economic factors that influence the HDI, such as poverty, unemployment, and education. This study aims to analyze the influence of these three factors on the HDI in Indonesia in the period 2014–2023. The approach used is a quantitative approach with a panel data regression analysis method. The data used are secondary data from official national sources, and data processing is carried out using EViews 13 software. The results of the analysis show that partially, the poverty and education variables have a significant influence on the HDI in Indonesia, while the unemployment variable does not have a significant effect. However, simultaneously, the three variables together have a significant effect on the HDI during the study period. This finding emphasizes the importance of strategies for improving education and poverty alleviation in efforts to improve the quality of life of the community. The novelty of this study lies in the coverage of more up-to-date post-pandemic data and the panel approach that provides a dynamic picture across time and region. These results provide policy implications that poverty reduction and increasing access to education need to be top priorities in human development planning in Indonesia.